THE EFFECT OF LAVENDER AROMATHERAPY ON DYSMENORRHOEA STUDENTS IN INSTITUTE OF HEALTH SCIENCE MEDICA PERSADA BALI - Pramita, AA Sg Dewi Pradnya; Sutema, IA Manik Partha; Putri, Dhiancinantyan Windydaca Brata (Journal Pharmaceutical Science and Application, 2020)
Background: Menstrual pain (dysmenorrhoea) is a symptom characterized by discomfort in the abdomen during menstruation. Lavender aromatherapy is beginning to be sought as one of the non-pharmacological therapies because the use of NSAIDs is reported to cause many side effects. The main components of lavender, linalool (35%) and linalyl acetate (51%) are efficacious as analgesics and maximally absorbed through the skin. Objective : This study aims to determine the effect of lavender aromatherapy on the menstrual pain of female college students at the Persada Medika Institute of Bali. Methods: Quasy experimental with one group pre-posttest design. The study was followed by 38 female students with moderate to severe pain using the random sampling technique. Data were analyzed using the non-parametric Wilcoxon test with p <0.05. Results: The results prior to lavender aromatherapy showed moderate pain at 73.7% and severe pain 26.3%. After lavender aromatherapy was administered, they showed moderate pain at 21% and mild pain at 79%. The Wilcoxon test indicated that the value of p = 0,000, where p <0.05. Conclusion: There is an effect of lavender aromatherapy to decrease menstrual pain (dysmenorrhoea) of female college students at the Persada Bali Institute of Health Sciences. Keywords : Aromatherapy Lavender, Dysmenorrhoea, Pain Scale, Linalool, Linalyl Acetate